SANTORIO SANTORIO – THE PIONEER OF EVIDENCE BASED MEDICINE - Gasparini, Mladen (Annales Kinesiologiae, 2015)
In everyday clinical practice there is a constant need for valid information about diagnosis, prognosis, therapy and prevention of a variety of diseases. But there could be a disparity between the physician’s diagnostic skills and his clinical judgment if he relies only on traditional sources of information. In the 1992, a group of scientists from the McMaster University in Ontario, Canada attempted to integrate individual clinical expertise with the best external evidence. They propose a process in which systematically finding, appraising and using of contemporaneous research were the base for proper clinical decision. They called this integration of personal clinical knowledge with research evidence – Evidence Based Medicine (EBM) and since then interest in this field has growing exponentially.  But 400 years before this important concept emerged a young physician from Koper, named Santorio Santorio (1561 – 1636) argued that a doctor should first rely on sense experience, then on reasoning, and only lastly on authority. Beside his numerous medical inventions he was the first to search justification to his practice by using some vital connection between measured parameters and a person’s health state. He could be therefore credited as one of the beginners of modern concepts of science or evidence based medicine.